Synthesis, characterization and Photocatalytic activity of Composite g-c3n4/gan-zno - Nguyen, Ha Trang (2020)
In chemistry, photocatalysis is the acceleration of a photoreaction in the presence of a catalyst. According to theory, the structure of matter consists of a region of molecular orbitals that are packed with enough electrons, called valence band (VB) and a region of molecular orbitals and electron drums, called conduction band (CB). These two regions are separated by an energy gap called the band gap energy, which is the energy difference between the VB and the CB. The difference between conductive, non-conductive and semi-conductive materials is the difference in the energy band gap value. Semiconductor material is an intermediate material between conductive material and non-conductive material. When excited enough by the energy (greater than the forbidden energy of Eg), electrons in the VB of the semiconductor material can pass the banding gap to the CB, becoming the semiconductors. All semiconductors can be the photocatalysts (Jie Xu et al., 2013). Therefore, to achieve an ideal photocatalyst, a semiconductor photocatalyst need to have a suitable band gap to harvest sufficient solar energy. However, the using 2 photocatalyts still face with some drawbacks, for example limited visible light utilization and low electron-hole separation efficiency as well as the stability. Recently, the combination of two types of materials are GaN – ZnO and graphite carbon nitrite g-C3N4 have been tested as photocatalysts. Compared to other photocatalysts, GaN – ZnO and g-C3N4 have many advantages such as low band gap energy, activating in visible light, high surface area, durable and can be synthesized in large quantities.